Novel miniaturized fluorescence loop-mediated isothermal amplification detection system for rapid on-site virus detection - Wu, Yanqi; Bai, Liping; Ye, Chengfu; Yuhong Guan,; Kunming Yan,; Chen, Hui; Jiang, Zhihong (Frontiers in Bioengineering and Biotechnology, 2022)
New pathogen outbreaks have progressed rapidly and are highly infectious in recent years, increasing the urgency of rapid and accurate detection of pathogenic microorganisms. Based on the point-of-care testing (POCT) requirements, in this study, a real-time fluorescent loop-mediated isothermal amplification (LAMP) detection system was developed and applied to pathogen detection. The system is compact and portable, with good uniformity and reproducibility, and it can detect pathogens rapidly and effectively. For norovirus detection, the linear range was 100–106 copies/μL. The system can achieve the theoretical sensitivity of LAMP detection, conclusions could be obtained within 35 min, and quantitative detection was possible. The test results of 45 clinical samples were consistent with quantitative PCR (qPCR) and clinical results, and the accuracy could reach 100%. This system has the characteristics of portability, speed, and POCT accuracy, and the cost is much lower than that of commercial qPCR. Therefore, it is suitable for remote areas or places with relatively poor conditions and environments requiring on-site conditions. It can also be widely used to detect various epidemics and unexpected diseases.